Automated irrigation system using solar power - Uddin, Jia; Reza, S.M. Taslim; Newaz, Qader; Uddin, Jamal; Islam, Touhidul; Kim, Jong-Myon (© 2012 IEEE, 2016)
This conference paper was presented in the 2012 7th International Conference on Electrical and Computer Engineering, ICECE 2012; Dhaka; Bangladesh; 20 December 2012 through 22 December 2012 [© 2012 IEEE] The conference paper's definite version is available at: :http://dx.doi.org/10.1109/ICECE.2012.6471527